(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
The article is devoted to the issues of object recognition in the image. The article provides information on the intermediate images of the images used in the recognition process and their approaches in determining the quality criterion. The effectiveness of the proposed method of recognizing land use objects is demonstrated in the example of a reservoir image using a new hybrid algorithm to identify surface water resources and their mineralization using satellite and drone images, and to identify images of agricultural plant species and increase the accuracy and reliability of satellite image classification. Recommendations for the creation of a system for the identification and monitoring of water bodies, systems and types of agricultural crops of the Republic of Uzbekistan using GIS technology.